2016
DOI: 10.3389/fmicb.2016.00201
|View full text |Cite
|
Sign up to set email alerts
|

Bioweathering Potential of Cultivable Fungi Associated with Semi-Arid Surface Microhabitats of Mayan Buildings

Abstract: Soil and rock surfaces support microbial communities involved in mineral weathering processes. Using selective isolation, fungi were obtained from limestone surfaces of Mayan monuments in the semi-arid climate at Yucatan, Mexico. A total of 101 isolates representing 53 different taxa were studied. Common fungi such as Fusarium, Pestalotiopsis, Trichoderma, and Penicillium were associated with surfaces and were, probably derived from airborne spores. In contrast, unusual fungi such as Rosellinia, Annulohypoxylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…isolated from variously coloured patinas of the Catacombs of St. Callistus and Priscilla in Rome (Italy) were the only fungi able to dissolve calcite when cultured on CaCO 3 glucose agar, while all Aspergillus and Penicillium isolates tested negative [ 27 ]. Compared to all previous research, a recent work of Ortega-Morales et al [ 36 ] showed the greatest percentage of fungi able to dissolve calcite, with more than 59% of fungi isolated from surface microhabitats of Mayan buildings testing positive when cultured on CMEA and CR2A-A selective media. As these two agarized nutrient media vary in composition with respect to the CaCO 3 glucose agar used, fungal carbonate solubilization activity presumably depends not only on environmental factors and origin of the isolates, but on available sources of carbon and nitrogen as well.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…isolated from variously coloured patinas of the Catacombs of St. Callistus and Priscilla in Rome (Italy) were the only fungi able to dissolve calcite when cultured on CaCO 3 glucose agar, while all Aspergillus and Penicillium isolates tested negative [ 27 ]. Compared to all previous research, a recent work of Ortega-Morales et al [ 36 ] showed the greatest percentage of fungi able to dissolve calcite, with more than 59% of fungi isolated from surface microhabitats of Mayan buildings testing positive when cultured on CMEA and CR2A-A selective media. As these two agarized nutrient media vary in composition with respect to the CaCO 3 glucose agar used, fungal carbonate solubilization activity presumably depends not only on environmental factors and origin of the isolates, but on available sources of carbon and nitrogen as well.…”
Section: Discussionmentioning
confidence: 72%
“…Albertano and Urzì [ 27 ] suggested that microfungi colonizing marble and limestone monuments use nutrients produced by phototrophic microorganisms to synthesize organic acids which dissolve CaCO 3 from the substrate. According to Sterflinger [ 32 ] and Ortega-Morales et al [ 36 ], only fungi that produce and secrete acids can dissolve CaCO 3 , and strong oxalic acid (C 2 H 2 O 4 ) is the main “culprit” in most instances. Since organic acids are synthesized, as a by-product of oxidative metabolism during primary fungal metabolism, it is no wonder that in our study and many others as well [ 9 , 34 , 36 ], a transparent zone of CaCO 3 dissolution was formed very early, i.e., during the first week of the incubation period.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the alteration and transformation of the lithomatrix by metabolism and bioweathering processes of phototrophs can be expected ( Weber et al., 2011 ). This was described for extreme habitats such as Antarctica or ancient Mayan buildings ( Ortega-Morales et al., 2016 ) and similar interactions are very likely to occur in the Atacama Desert, but reports are still missing. Single processes of biogeophysical and biogeochemical weathering by (cyano-)bacteria, green algae, lichens, and fungi are well studied (reviewed in Salvadori and Municchia, 2016 ; Chen et al., 2000 ).…”
Section: Introductionmentioning
confidence: 82%
“…Oxalate-rich coatings occur globally and have been identified at a multitude of rock art sites, usually via chemical studies of rock paints. There is considerable evidence that oxalates in rock coatings are biogenic, the byproduct of bacteria (Bonaventura et al 1999; Hess et al 2008; Rusakov et al 2015), fungi (Gadd et al 2014; Monte 2003; Ortega-Morales et al 2016), lichens (Del Monte and Sabbioni 1987; Russ et al 1996), and mixed microbial communities (Gorbushina 2007). Evidence suggests that all carbon in oxalate biofilms originates from atmospheric carbon dioxide (Beazley et al 2002) and that, once formed, there is no carbon exchange with the substrate (Watchman 1993).…”
Section: Experimental Strategiesmentioning
confidence: 99%